Comparison of an Implantable Middle Ear Microphone and Conventional External Microphone for Cochlear Implants: A Clinical Feasibility Study. Issue 10 (14th December 2022) - Craddock, Louise C.; Hodson, James; Gosling, Amy; Cooper, Stacey; Morse, Robert P.; Begg, Philip; Prokopiou, Andreas; Irving, Richard M.
Abstract : Objectives: All commercially available cochlear implant (CI) systems use an external microphone and sound processor; however, external equipment carries lifestyle limitations. Although totally implantable devices using subcutaneous microphones have been developed, these are compromised by problems with soft tissue sound attenuation, feedback, and intrusive body noise. This in vivo pilot study evaluates a middle ear microphone (MEM) that aims to overcome these issues and compares hearing performance with that of an external CI microphone. Design: Six adult participants with an existing CI were implanted with a temporary MEM in the contralateral ear. Signals from the MEM were routed via a percutaneous plug and cable to the CI sound processor. Testing was performed in the CI microphone and MEM conditions using a range of audiometric assessments, which were repeated across four visits. Results: Performance of the MEM did not differ significantly from that of the CI on the assessments of Auditory Speech Sounds Evaluation loudness scaling at either 250 or 1000 Hz, or in the accuracy of repeating keywords presented at 70 dB. However, the MEM had significantly poorer aided sound-field thresholds, particularly at higher frequencies (≥4000 Hz), and significantly poorer performance on Arthur Boothroyd words presented at 55 dB, compared with the CI. Conclusion: In this pilot study, the MEM showed comparable performance to that of an external CI microphone across some audiometric assessments. However, performance with the MEM was poorer than the CI in soft-level speech (55 dB) and at higher frequencies. As such, the benefits of MEM need to be considered against the compromises in hearing performance. However, with future development, MEM is a potentially promising technology.